ANALISIS KONVERGENSI PERTUMBUHAN EKONOMI NEGARA-NEGARA ASEAN - Sorta Yemima Meilyana Siahaan (Jurnal Pendidikan Ekonomi Indonesia, 2023)
n ASEAN countries in 2011-2020. The data in this study uses secondary data, namely GDP per capita, unemployment rate, foreign direct investment, and economic openness in ASEAN countries in 2011-2020. The data in this study were obtained from publications on the Worldbank website with a sample of 6 countries during 2011-2020. The analytical tools used in this study are sigma convergence analysis (σ-convergence) and beta convergence analysis (β-convergence) which consist of absolute convergence and conditional convergence. The results of this study show that there is sigma convergence and conditional convergence (absolutely and conditionally) in economic growth in ASEAN countries in 2011-2020. The foreign direct investment and economic openness variables have a significant positive effect, while the unemployment rate has no significant effect on the convergence of economic growth in ASEAN countries in 2011-2020.